1984
DOI: 10.1002/hep.1840040623
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Interactions Between H2-Receptor Antagonists and Ethanol Metabolism in Man and in Rats

Abstract: The influence of a 7-day medication of either cimetidine (1,000 mg per day) or ranitidine (300 mg per day) on serum ethanol concentrations after a single oral dose of ethanol (0.8 gm per kg body weight) was investigated in a randomized placebo-controlled study in eight male volunteers. Compared with the placebo, cimetidine but not ranitidine produced a significant increase in both the peak serum ethanol concentration (85.9 +/- 3.5 vs. 73.0 +/- 3.2 mg dl-1, p less than 0.02) and in the area under the serum etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 24 publications
0
31
1
Order By: Relevance
“…The differences in the dose of cimetidine might also be a factor. Thus, the dose used by Feely & Wood (1982) was 1.25 times, and that used by Seitz et al (1983Seitz et al ( , 1984) was 1.5 times higher than the dose used in the present study. In addition, the type of ethanol beverage and food intake may have affected the rate and the extent of ethanol absorption by changing gastric emptying rate.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The differences in the dose of cimetidine might also be a factor. Thus, the dose used by Feely & Wood (1982) was 1.25 times, and that used by Seitz et al (1983Seitz et al ( , 1984) was 1.5 times higher than the dose used in the present study. In addition, the type of ethanol beverage and food intake may have affected the rate and the extent of ethanol absorption by changing gastric emptying rate.…”
Section: Discussioncontrasting
confidence: 58%
“…They suggested that this increase was due to inhibition of ethanol metabolism by cimetidine. Seitz et al (1983Seitz et al ( , 1984 also found increased plasma ethanol concentrations and AUC values after cimetidine but not after ranitidine. Tan et al (1983) speculated that cimetidine may increase the absorption rate of ethanol by increasing gastric emptying.…”
Section: Discussionmentioning
confidence: 89%
“…The existence of FPM may explain the fact that following an oral dose of ethanol, blood ethanol concentrations are significantly lower than blood levels following intravenous administration of the same dose of ethanol [6,7]. Gastric ADH activity and FPM of ethanol are affected by various factors including gender [2,4], ethnology [8][9][10], age [4,11,12], medication [3,13,14], gastric morphology [15,16], and the concentration of ethanol in the alcoholic beverage [17,18]. Furthermore, FPM of ethanol is also influenced by the gastric emptying time [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…This analysis does not include one study, 25 because the fed or fasted status was not described. Regardless of food intake, cimetidine and ranitidine resulted in modestly higher serum 28 C,R 10 Fasted 0.5 DiPadova et al 2 C,R,F 6 Fed 0.3 Dobrilla et al 24 C 6 C,R,F 12 Fed 0.3 Fraser et al 4 C,R,F 23 Fed 0.8 Fraser et al 18 R 20 Fed 0.3 Guram et al 3 C,R,F,N 6 Fed 0.75 Hernandez-Munoz et al 14 C,F 5 Fed 0.15 Jonsson et al 27 C,R 12 Fasted 0.8 Kendall et al 20 C,R,F 24 Fed 0.5-0.8 Mallat et al 15 C,R,F 12 Fed 0.3 Palmer et al 17 C 23 Fed 0.15 Palmer et al 17 C,R,N 23 Fed 0.15 Papke et al 26 C 10 Fasted 0.8 Raufman et al 5 C,R,F,N 23 Fed 0.3 Seitz et al 13 C,R 8 Fed 0.8 Sharma et al 16 C 11 Fed 0.3 Tanaka & Nakamura 22 C,R,F 6 Fasted 0.8 Toon et al 29 R 18 Fed/Fasted 0.5 Webster et al 25 C,R 7 Not 0.7 * C indicates cimetidine; R, ranitidine; F, famotidine; N, nizatidine. alcohol levels, while famotidine had no effect.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] Twenty-four trials were eligible for this meta-analysis. [1][2][3][4][5][6][12][13][14][15][16][17][18][19][20][24][25][26][27][28][29][30] Several studies administered more than one drug. These trials are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%